MAKAR DALAM TEKS SATUA I GLIJAH ANALISIS WACANA KRITIS - Bagus Wahyu Sudhyatmika; I Nyoman Suarka; I Ketut Jirnaya (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
This research examines the Satua (story) of I Glijah. This elder tells the story of a people who come into conflict with a king who likes to oppress the people. The people succeeded in killing the king in various ways. Finally the people were appointed to be the new king. This study uses Van Dijk's critical discourse analysis theory. This research will look at the form of treason, and its context. As a result, this story depicted a hidden form of treason with the king. This story context is a form of protest against closed social stratification.Key words: story, text, context